2010
DOI: 10.2527/jas.2009-1797
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of a steroidal implant and zilpaterol hydrochloride on feedlot performance, carcass characteristics, and skeletal muscle messenger ribonucleic acid abundance in finishing steers1

Abstract: This experiment investigated the effects of zilpaterol hydrochloride (ZH) and the steroidal implant Revalor-S (RS; 120 mg of trenbolone acetate and 24 mg of estradiol-17beta) on finishing steer performance and the mRNA concentration of beta-adrenergic receptors (beta-AR) types I and II, and types I, IIA, and IIX myosin heavy chain (MHC) isoforms. A total of 2,279 feedlot steers weighing 426 +/- 6.4 kg were administered no implant or RS on d 0, and fed 0 or 8.3 mg of ZH/kg of diet DM during the last 30 d with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 26 publications
8
26
1
3
Order By: Relevance
“…54 Although consumers detected differences in the Longissimus dorsi muscle juiciness for both ZH treatments, the overall pleasing rating was unaffected (P = 0.046; Wald c 2 test = 6.2; d.f = 1). This agrees with the results of Garmyn 36 , who indicated that ZH does not modify Longissimus dorsi muscle taste from Holstein bulls compared with control samples. Despite sustained juiciness and general softness scores being affected, it is likely that these latter changes were related to the lesser amount of intramuscular fat in the ZH-treated animal meat.…”
Section: Generic Zilpaterol Hcl In Bos Indicussupporting
confidence: 92%
See 1 more Smart Citation
“…54 Although consumers detected differences in the Longissimus dorsi muscle juiciness for both ZH treatments, the overall pleasing rating was unaffected (P = 0.046; Wald c 2 test = 6.2; d.f = 1). This agrees with the results of Garmyn 36 , who indicated that ZH does not modify Longissimus dorsi muscle taste from Holstein bulls compared with control samples. Despite sustained juiciness and general softness scores being affected, it is likely that these latter changes were related to the lesser amount of intramuscular fat in the ZH-treated animal meat.…”
Section: Generic Zilpaterol Hcl In Bos Indicussupporting
confidence: 92%
“…The magnitude of improvement in final body weight (22 %), lies near the maximum value reported in the literature (25 %), using the reference brand ZH. 4,[31][32][33][34][35][36][37][38][39] For example, weight gain coincides greatly with other studies conducted on Bos taurus bulls. 34,40 Elam et al treated Bos taurus bulls with 8.33 mg ZH/kg feed as dry matter for 30 days and obtained final weight increments of 9.3 kg compared with untreated bulls.…”
Section: Generic Zilpaterol Hcl In Bos Indicussupporting
confidence: 85%
“…Why this occurred is unclear, as fibre populations were similar in the ST muscles of control steers of each breed. b-AA and IMP can be additive on carcass characteristics (Strydom et al 2009;Baxa et al 2010), but RAC and the hormonal effects of IMP have not been shown to be synergistic (Bass et al 2009). Gonzalez et al (2010) incorporated different breeds into a study on the effect of RAC on muscle fibre morphology, but were unable to assess breed effect as it was confounded with kill group.…”
Section: A Bmentioning
confidence: 99%
“…Kellermeier et al (2009) conducted a similar study in steers and reported that average muscle fiber diameter increased by 3% and 6% when anabolic implants and ZH were utilized, respectively. While Rathmann et al (2009) and Baxa et al (2010) did not directly measure fiber CSA or diameter, they did indicate increases in the mRNA expression of type IIX muscle fibers demonstrated ZH increased protein synthesis of this isoform. Other B-AA have also increased muscle fiber CSA.…”
Section: Growth-promoting Technologies Effectsmentioning
confidence: 99%